Gaining political will for actions to achieve health equity: lessons from Australia for advocates. (30th September 2020) - Baum, F; Townsend, B; Fisher, M; Freeman, T; Harris, P; Browne-Yung, K; Friel, S
Abstract: Background: There has been an accumulation of evidence on the importance of action on the social determinants of health to reduce global and national health equity. Yet there has been little effective systematic action by governments. This is commonly attributed to the absence of political will. Despite its importance, however, little research has examined how political will might be created or prevented. Methods: This paper reports on the results of eight case studies of the extent to which Australian public policy is likely to contribute to reducing health inequities. 192 participants were interviewed including public servants, politicians and their staff, non-government organisation workers and community members. The transcripts were interrogated with the assistance of NVivo software to determine lessons about the creation or destruction of political will. The case studies were of: national primary health care policy, crucial determinants of health (work conditions, internet access, urban planning, social welfare, trade) and an automotive plant closure. Results: We found the following factors to be important in determining the extent of political will for health equity, whether: path dependency was present; the issue would impact on staying in or winning government; political philosophies stressed collectivism or individualism; there were negative or positive social constructions of groups affected by the policies; economic and/or biomedical framings were dominant; elites (especially business interests) lobbied against the policies; and there was effective civil society and policy advocacy in favour of the policies. Conclusions: Building on our insights from our case studies of action for political will, we conclude with a series of questions to guide the work of public health activists and policy advocates working to support existing and to create new political will in multiple contexts. Key messages: The creation of political will is vital to the adoption of policies supportive of health equity. Analysis of 8 policy case studies points to how advocacy can most effectively create political will.